ALT Donor Area Compartment Syndrome: A Rare and Devastating Complication - Gloria Alsina; Teresa Nunez-Villaveirán; Daniel Camporro; Clara Martin (Indian Journal of Plastic Surgery)
We present two cases of acute compartment syndrome (ACS) in the donor area of an anterolateral thigh (ALT) flap, with extensive necrosis of the quadriceps muscle. An innervated latissimus dorsi (LD) flap was used to cover the defect and restore functionality of the lower extremity. ACS in the ALT donor area is extraordinarily uncommon. Its mechanism seems to be multifactorial, being more frequent in young athletic males and, possibly, in patients with anatomical vascular variations. It is important to detect it promptly to prevent irreversible muscular ischemia. Intense pain is an alarm sign but might be absent in patients with epidural infusion pumps. We recommend caution with the use of this analgesia and frequent monitoring of the donor area during the early postoperative period. The free functional LD muscle flap is an option to treat full-thickness quadriceps damage, allowing for wound closure, soft-tissue coverage, and restoration of the knee extension movement.